BERPIKIR KREATIF SISWA DALAM MENYELESAIKAN MASALAH MATEMATIKA DI MASA PANDEMI COVID-19 - Eko Syaiful Anwar; Teguh Wibowo; Isnaeni Maryam (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2021)
The aim of the research is to describe students creative thinking in solving mathematical problems during the pandemic Covid 19. The type of this research is descriptive research with a phenomenological approach. A subject chosen by using purposive technique. The subject of research consisting from 2 students with high ability. Data collection techniques using test, interviews, and field notes. The research instrument was in the form of student’s creative thinking test on geometry material and interview guidelines. The validity of data with triangulation technique. The result of this research is student with high ability have creative thinking level 3 (creative). The student were able indicator fluency and flexibility. Indicator of fluency is characterized by ability of students to provide answers that are diverse and is true. While, the indicator of flexibility is characterized by ability of students to use different methods or approaches in solving mathematical problem and is true value.